Associations of Musculoskeletal Pain With Mobility in Older Adults: Potential Cerebral Mechanisms. (13th May 2017) - Cruz-Almeida, Yenisel; Rosso, Andrea; Marcum, Zachary; Harris, Tamara; Newman, Anne B; Nevitt, Michael; Satterfield, Suzanne; Yaffe, Kristine; Rosano, Caterina; ,
Abstract: Background: Musculoskeletal pain is highly prevalent and limits mobility in older adults. A potential mechanism by which pain affects mobility could be through its negative impact on the brain. We examined whether structural integrity of cerebral gray and white matter (WM) mediated the relationship between pain and mobility in community-dwelling older adults. Methods: Musculoskeletal pain, gait speed, and neuroimaging data were obtained concurrently from the Health ABC study (mean age = 83/56% female, n = 212). Microstructural gray matter integrity was measured by mean diffusivity (MD), WM microstructure and macrostructure were measured by fractional anisotropy (FA) and WM hyperintensities (WMH), respectively. Regression models were adjusted for gray matter atrophy, age, gender, medication use, and obesity. Bootstrapped mediation methods were used (1, 000 bootstrapped samples, 95% confidence intervals). Results: The associations of musculoskeletal pain with WMH (β = .19, p < .05) and FA (β = −.18, p < .05) were robust to adjustment for gender, medication use, age, body mass index (BMI), and brain atrophy. Participants who experienced both knee and back pain had a significantly slower gait speed ( 0.11 m/s) than those without knee or back pain ( p < .05) independent of gender, medication, age, and BMI. WMH and FA significantly mediated the pain–gait speed relationship. Associations between pain and MD were not significant, and MD did not modify the association between pain and gait speed. Conclusions: Cerebral WM integrity may contribute to the detrimental effects of musculoskeletal pain on mobility, although pre-existing WM integrity may also simultaneously amplify pain and decrease mobility. Future studies are needed to further understand whether successful pain management may significantly improve both brain health and mobility.